'Drip-and-ship' intravenous thrombolysis and outcomes for large vessel occlusion thrombectomy candidates in a hub-and-spoke telestroke model. (29th July 2021) - Regenhardt, Robert W; Rosenthal, Joseph A; Awad, Amine; Martinez-Gutierrez, Juan Carlos; Nolan, Neal M; McIntyre, Joyce A; Whitney, Cynthia; Alotaibi, Naif M; Dmytriw, Adam A; Vranic, Justin E; Stapleton, Christopher J; Patel, Aman B; et al.
Abstract : Background: Randomized trials have not demonstrated benefit from intravenous thrombolysis among patients undergoing endovascular thrombectomy (EVT). However, these trials included primarily patients presenting directly to an EVT capable hub center. We sought to study outcomes for EVT candidates who presented to spoke hospitals and were subsequently transferred for EVT consideration, comparing those administered alteplase at spokes (i.e., 'drip-and-ship' model) versus those not. Methods: Consecutive EVT candidates presenting to 25 spokes from 2018 to 2020 with pre-transfer CT angiography defined emergent large vessel occlusion and Alberta Stroke Program CT score ≥6 were identified from a prospectively maintained Telestroke database. Outcomes of interest included adequate reperfusion (Thrombolysis in Cerebral Infarction (TICI) 2b–3), intracerebral hemorrhage (ICH), discharge functional independence (modified Rankin Scale (mRS) ≤2), and 90 day functional independence. Results: Among 258 patients, median age was 70 years (IQR 60–81), median National Institutes of Health Stroke Scale (NIHSS) score was 13 (6-19), and 50% were women. Ninety-eight (38%) were treated with alteplase at spokes and 113 (44%) underwent EVT at the hub. Spoke alteplase use independently increased the odds of discharge mRS ≤2 (adjusted OR 2.43, 95% CI 1.08 to 5.46, p=0.03) and 90 day mRS ≤2 (adjusted OR 3.45, 95% CI 1.65 to 7.22, p=0.001), even when controlling for last known well, NIHSS, and EVT; it was not associated with an increased risk of ICH (OR 1.04, 95% CI 0.39 to 2.78, p=0.94), and there was a trend toward association with greater TICI 2b–3 (OR 3.59, 95% CI 0.94 to 13.70, p=0.06). Conclusions: Intravenous alteplase at spoke hospitals may improve discharge and 90 day mRS and should not be withheld from EVT eligible patients who first present at alteplase capable spoke hospitals that do not perform EVT. Additional studies are warranted to confirm and further explore these benefits.